Endoscopic ultrasound-guided choledochoduodenostomy results in fewer complications than percutaneous drainage following failed ERCP in malignant distal biliary obstruction - de Jong, Mike J.P.; van Delft, Foke; van Geenen, Erwin-Jan M.; Bogte, Auke; Verdonk, Robert C.; Venneman, Niels G.; Vrolijk, Jan Maarten; Straathof, Jan-Willem A.; Voermans, Rogier P.; Bijlsma, Rina A.; Kuiken, Sjoerd D.; Quispel, Rutger; Hadithi, Muhammed; Basiliya, Kirill; Vleggaar, Frank P.; Bisseling, Tanya M.; de Wijkerslooth, Thomas R.; Bruno, Marco J.; van Wanrooij, Roy L.J.; Siersema, Peter D. (Endoscopy, 2025)
Percutaneous transhepatic biliary drainage (PTBD) and endoscopic ultrasound-guided biliary drainage (EUS-BD), including choledochoduodenostomy (EUS-CDS), are alternative methods for biliary drainage in patients with distal malignant biliary obstruction (MBO) after failed endoscopic retrograde cholangiopancreatography (ERCP). Data on long-term outcomes, adverse events (AEs), and quality of life (QoL) after EUS-CDS and PTBD are limited. Therefore, we created a registry to evaluate the outcomes of both drainage procedures.Patients with distal MBO who underwent EUS-CDS or PTBD after unsuccessful ERCP were included in this multicenter investigator-initiated prospective registry over an 18-month inclusion period. Primary end points were procedure-related AEs and mortality within 90 days post-procedure. Secondary end points included technical and clinical success, reinterventions, hospital stay, and QoL.55 patients were included, with 12 patients undergoing PTBD (technical success 100%) and 43 patients EUS-CDS (technical success 97.7%). Prior to ERCP, 7/12 patients in the PTBD group and 12/43 patients in the EUS-CDS group opted for best supportive care. The 90-day mortality rate was 66.7% in the PTBD group and 20.9% in the EUS-CDS group (P = 0.005). Furthermore, 11/12 patients (91.7%) in the PTBD group and 19/43 (44.2%) in the EUS-CDS group developed one or more AEs (P = 0.004). The median post-procedural hospital stay was 4 days (interquartile range [IQR] 2–6) in the PTBD group vs. 1 day (IQR 1–2) in the EUS-CDS group (P = 0.001).When both modalities were available and technically feasible, gastroenterologists preferred EUS-CDS over PTBD. EUS-CDS seems to be associated with lower mortality and AE rates, shorter hospital admission, and fewer reinterventions, but a randomized controlled trial should confirm these observations.